Hubungan Antara Kecepatan, Kepadatan, dan Volume di Ruas Jalan Kolonel H. Burlian Palembang - Adelia Lestari; Ramadhani Ramadhani; Pujiono Pujiono (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Traffic congestion is a common problem in big cities, including on Jalan Kolonel H. Burlian Palembang. This study aims to determine the relationship between speed, density, and traffic volume and utilize Google Traffic technology in speed data collection. The research method used is a quantitative approach with primary data collection through field surveys and secondary data from data retrieved using the Application Programming Interface (API) from the Google Traffic server. The results of the study indicate that the comparison of vehicle speeds between the field survey and the Google Traffic approach does not show a significant difference. The T-test results obtained a p-value (two tail) of 0.999998532 ( > 0.05). Modeling with Greenshield theory produces a valid linear relationship between these variables, with an error value (RMS error) that is still within reasonable limits. This study shows that Google Traffic can be used as an alternative measurement in traffic analysis under certain conditions.